2012
DOI: 10.1038/ijo.2012.128
|View full text |Cite
|
Sign up to set email alerts
|

High fat/carbohydrate ratio but not total energy intake induces lower striatal dopamine D2/3 receptor availability in diet-induced obesity

Abstract: High-energy diets that induce obesity decrease striatal dopamine D 2/3 receptor (DRD 2/3 ) availability. It is however poorly understood which components of these diets are underlying this decrease. This study assessed the role of saturated fat intake on striatal DRD 2/3 availability. Forty rats were randomized to a free-choice high-fat high-sugar diet (HFHS) or a standard chow diet for 28 days. Striatal DRD 2/3 availability was measured using 123 I-IBZM storage phosphor imaging at day 29. The HFHS group was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 19 publications
8
29
0
Order By: Relevance
“…Here, we investigated the hypothesis that diet-induced obesity causes physical inactivity via deficits in striatal DA transmission. Consistent with previous work, we found that chronic high-fat diet decreased striatal D2R binding (Hajnal et al, 2008; Huang et al, 2006; Narayanaswami et al, 2013; van de Giessen et al, 2012; van de Giessen et al, 2013). We also observed a deficit in motor-related firing of striatal neurons in obese mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we investigated the hypothesis that diet-induced obesity causes physical inactivity via deficits in striatal DA transmission. Consistent with previous work, we found that chronic high-fat diet decreased striatal D2R binding (Hajnal et al, 2008; Huang et al, 2006; Narayanaswami et al, 2013; van de Giessen et al, 2012; van de Giessen et al, 2013). We also observed a deficit in motor-related firing of striatal neurons in obese mice.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, factors such as sleep duration (Wiers et al, 2016) and caffeine intake (Volkow et al, 2015) can also affect D2R binding, and are not reported or controlled in most clinical studies. These sources of variance can be mitigated in animal studies, which paint a consistent picture of reductions in D2R mRNA (Mathes et al, 2010; Zhang et al, 2015), protein (Adams et al, 2015; Johnson and Kenny, 2010), and receptor binding (Hajnal et al, 2008; Huang et al, 2006; Narayanaswami et al, 2013; van de Giessen et al, 2012; van de Giessen et al, 2013) in obese rodents. Our work extends this body of literature by reporting that other aspects of DA signaling remain unchanged in obese mice, even those with reductions in D2Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Following diet exposure, both DIO-prone and DIO-resistant rats displayed cross-sensitization to amphetamine and down-regulation of striatal dopamine D2 receptors (D2Rs). Thus, while enhanced food cue reactivity precedes obesity and may confer vulnerability to overeating and diet-induced weight gain, other adaptations in dopamine function may occur as a direct consequence of palatable diet consumption, regardless of weight gain [36]. …”
Section: Metabolic Control Of Food Cue Reactivity In the Nucleus Accumentioning
confidence: 99%
“…Of the opioid-expressing neurons, enkephalin (ENK) neurons are of specific interest as they express dopamine D2 receptors and have been linked to high-fat feeding, i.e., Acb enkephalin gene expression is affected by consumption of the highly palatable Ensure drink (17), which contains fat and sugar, and striatal D2 receptor availability is correlated with high-fat intake (18). Moreover, enkephalin binds to mu-opioid receptors and local Acb administration of the mu-opioid receptor agonist DAMGO specifically increases intake of high-fat foods (19).…”
mentioning
confidence: 99%